Establishing Geographies of Children and Young People - Skelton, Tracey; Aitken, Stuart C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
Children's and young people's geographies is one of the most recent sub-disciplines within human geography. It has rapidly developed to a level of critical mass which includes established academic work, key names within academia, growing numbers of graduate students, expanding numbers of university level taught courses, as well as national and international training programmes focusing on younger people. In addition to the journal Children's Geographies, all the major academic presses have published monographs, textbooks and edited collections focusing on children and young people. However, the largest international collection of scholarly work on geographies of children and young people is now available through the Springer Major Reference Work, Geographies of Children and Young People. This edited collection comprises twelve volumes containing almost 300 chapters. The volumes and sections are structured by themes, which reflect the broader geographical debates, geographical diversity, and scholarly expertise of 24 editors and chapter contributors.
Affective geo-visualization and children: Representing the embodied and emotional geographies of children -- An Aporia to Theory -- Approaching Child and Youth Geographies through Darwin -- Babies and their Spacialities: Contributions to Studies of Babies -- Changing the Subject: Education and the Constitution of Youth in the Neoliberal Era -- Children's Emotional and Affective Geographies -- Engaging with Bourdieu: A Review of the Utilisation of Bourdieu within Children's Geographies -- Foucault, Mischievous Children and Unruly Geographies -- Geographies of Architecture, Children's Geographies and Nonrepresentational Theory -- Geographies of Child Labour and Children's Work -- Geographies of Education: Context, Case and Future Directions -- Geographies of Youth Religiosity and Spirituality -- Illustration, Challenge or Alternative Perspective: Global South Research and the New Social Studies of Childhood -- Intergenerational Geographies in Theory and Practice -- Internationalization of Education: Key Developments and Debates -- Living in the Space Between: Object-Relations Psychoanalysis and the Geography of Subjective Experience -- Paradoxes of Young People's Political Participation -- Play and Playgrounds in Children's Geographies -- Social Reproduction and the Shifting Geographies of Children and Childhood -- Spinoza and the Spider: Theorizing Childhood as Capacities of Affection and Affect -- Taking Seriously Everyday Life Inquiry : Youth Participatory Action Research & Theory -- The Political Geography of the 'Best Interest of the Child' -- Theorizing Children's Political Agency -- Zero Tolerance for Millennials: Care, Violence and the Development of Young People's and Children's Geographies.
Keywords: Human geography; Sociology; Social groups; Human Geography; Sociology of Family, Youth and Aging; Sociological Theory